ANALYSIS OF STUDENTS ECOLOGICAL INTELLIGENCE - Rani Tania Pratiwi; Disman Disman; Nana Supriatna; Erlina Wiyanarti; Deden Agustira (Universitas Ahmad Dahlan, 2020)
In December 2018, Kuningan University launched the Green Campus. The eco - campus program is motivated by, among others, that the campus environment is expecting to be a comfortable, clean, shady (green), beautiful, and healthy place to gain knowledge. The campus environment as an inseparable part of the urban ecosystem is not insignificant in its role and contribution to increasing or reducing global warming. Besides that, what is also important is how the campus community can implement Environmental Science and Technology in a Real Field. Therefore the Eco-Campus program is aimed at increasing the awareness and concern of the campus community as a collection of scientific societies to participate and be responsible for reducing Global Warming. However, er, of all these issues, the most important thing is how we can apply the concept in our daily behavior better known as green behavior, then how this behavior can be transmitted and taught in the context of education. Sometimes we think too hard about behaviors like what can say green behavior